Geology for dummies - Spooner, Alecia M. (Hoboken, NJ : Wiley, 2011)
"Get a rock-solid grasp on geology ... Whether you're looking to supplement classroom learning or are simply interested in earth sciences, this guide gives you a straightforward introduction to the study of the earth, its materials, and its processes"--P. [4] of cover.
Studying the earth -- Elements, minerals, and rocks -- One theory to explain it all : plate tectonics -- Superficially speaking : about surface processes -- Long, long ago in this galaxy right here -- The part of tens.
Includes index.
Keywords: Geology -- Popular works; Geologie; Geology; Geologie